Implementasi dan Implikasi Asas Kekhususan Sistematis pada Tindak Pidana Telekomunikasi - Triana Dewi Seroja; Winda Fitri (Universitas Internasional Batam, 2019)
Abstract The purpose of this research is to analyze and to find the implementation and implication of special systematical principle (lex specialis systematic) in cases of violations of the law committed by telecommunication corporations. This research uses the legal normative approach. It is a research method conducted by analyzing secondary data and utilizing a analytical descriptive. Based on the results of the analysis, it was found that the implementation of Anti-Corruption law in this regard is less precise. This kind of offense should fall under the Telecommunication law because the subject, object, and cause and effect of the violation are governed heavily by Telecommunication law. And the legal implications of the implementation of the Anti-Corruption Law generates legal uncertainty in law enforcement. This research offers a solution by fabricating a technical guideline in the enforcement of lex specialis systematic for the laws that contain the said special characteristic as a handbook when confronted by cases that hold the potential falling under several laws.